The Effect of Hypnoparenting in Overcoming the Problem of Smart Device Addiction in Preschool Children at Ar Raudah Kindergarten Banjarmasin - Esme Anggeriyane; Suci Fitri Rahayu (Universitas Muhammadiyah Yogyakarta, 2022)
Background: The unwise use of smart devices in children negatively impacts psychosocial and physical health. Hypnoparenting is a communication technique involving the brain activity system between parents and children.Objective: This research aims to determine the effect of hypnoparenting in overcoming the problem of smart device addiction in preschool children.Methods: The study used a quasi-experiment design with a time-series experiment on 40 parents. A sample included 19 parents of preschool children at Ar Raudah Kindergarten Banjarmasin with a purposive sampling technique in August 2021. Inclusion criteria were parents with children with smart device addiction problems who have never applied hypnoparenting. Exclusion criteria included parents who were unable to accompany their children to sleep daily. The Independent variable was hypnoparenting, while the dependent variable was smart device addiction. The research instrument was an interview guide and observation sheet.Result: The results showed that there were 2 people (10,53%) with a low level of smart device addiction before hypnoparenting was carried out, 11 people (57.89%) with a moderate level, and 6 people (31,58%) with a high level. After hypnoparenting was carried out, there were 11 people (57.89%) with a low category, 7 people (36,84%) with a moderate category, and 1 person (5,26%) with a high category. The data analysis was conducted using the Wilcoxon Signed Ranks Test with ρ value = 0.009 0.05.Conclusion: The result showed a significant effect of hypnoparenting carried out for 21 days on smart device users. Hypnoparenting could be applied by parents for 21 days before bedtime to overcome the problem of smart device addiction to optimize growth and development in preschoolers.